Case reportAnaesthetic management for liver resection in a patient with myelodysplastic syndrome - Kostopanagiotou, Georgia; Stamatakis, Manolis; Coussi, Theofili; Matsota, Paraskevi; Smyrniotis, Vassilios; Pandazi, Ageliki (Archives of Medical Science, 2008)
We describe the anaesthetic management of a patient with myelodysplastic syndrome undergoing liver resection. Despite vitamin K, platelet (PLT), fresh frozen plasma (FFP), methylprednisolone, desmopressin and aprotinin administration, bleeding occurred after hepatectomy and was treated with tamponade, PLT and FFP. The patient was extubated on the 1st postoperative day. On the 11th postoperative day the patient developed fever with shivering, haemodynamic instability and reduced PLT number due to a systemic infection by Staphylococcus aureus. During his hospitalization the patient received 27 units of red blood cells, 55 units of FFP and 233 units of platelets in total.